Pencegahan Bullying: Pendekatan Edukasi dan Psikososial di Sam Tengku Ampuan Jemaah Sungai Besar Selangor Malaysia - Muh. Nur Rochim Maksum; Nurul Latifatul Inayati; Wachidi; Athia Tamyizatun Nisa; Izzun Khoirun Nissa; Lukman Harahap; Viky Nur Vambudi; Alfan Rifai; Abil Fida Muhammad Qois Al Hadi; Ade Kurniawan; Lokahita Reangeli Cahyani; Galih Anisa Fala; Nadia Zakia Al ‘Ulya; Hanida Putri; Nanda Ayu Walhidayah; Jumingan; Lintang Faza Muqoddas (JURPIKAT, 2026)
Bullying in Malaysian secondary schools is a crucial issue due to the low awareness and readiness of teachers in handling cases. This service focuses on the prevention of bullying at SAM Tengku Ampuan Jemaah through an educational and psychosocial approach. The goal is to raise awareness of the dangers of bullying and equip teachers with social-emotional skills to create a safe school environment. The method applied is experiential learning through the Workshop "Building Safe Schools" with Psychological First Aid (PFA) material and the integration of spiritual values. The results showed a significant increase in the capacity of 24 participating teachers, with an average increase in understanding of 19.78% (from 3.64 to 4.36). The positive impact is to strengthen the role of teachers as safe adults who are able to carry out initial interventions in an empathetic and systematic manner, in order to encourage the creation of an inclusive and violence-free school culture.